2015
DOI: 10.2147/opth.s91486
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of pneumatic retinopexy for primary treatment of rhegmatogenous retinal detachment

Abstract: BackgroundPneumatic retinopexy (PR) remains a popular technique for the treatment of rhegmatogenous retinal detachment (RRD).ObjectiveTo evaluate the single operation and final success rate of PR for primary treatment of RRD and to determine factors associated with anatomical and visual outcomes.MethodsThis retrospective case review study analyzed the data of patients who underwent PR for primary treatment of RRD. Patients with a follow-up period of <2 months were excluded. Single operation success was defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Later, authors have found it to vary between 60% and 82%. [ 7 8 9 10 11 12 ] Table 5 lists the major studies and their results of PR. Our SOSR of 60% is toward the lower side due to the inherent biases in a retrospective study and uncontrolled parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Later, authors have found it to vary between 60% and 82%. [ 7 8 9 10 11 12 ] Table 5 lists the major studies and their results of PR. Our SOSR of 60% is toward the lower side due to the inherent biases in a retrospective study and uncontrolled parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of those preferring PR has remained stable at 25% [14]. In recent years, PR has become a less popular method for treating pseudophakic RD [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…SB, which conventionally provides target-oriented retinal attachment, is one of two basic methods in the surgical treatment of RD. SB had the highest success rate and was the most frequently used method in the treatment of RD before the advancements in PPV technique [5][6][7][8][9][10][11][12][13][14][15][16][17]. The most significant advantage of PPV is that peripheral vitreous detachment can be visualized more clearly by eliminating vitreous and posterior hyaloid membrane.…”
Section: Discussionmentioning
confidence: 99%
“…A retinal tear is a full-thickness break in the retina that, if left untreated, may lead to rhegmatogenous retinal detachment (RRD) [ 1 ]. The majority of retinal tear formation is the result of posterior vitreous detachment [ 2 ].…”
Section: Introductionmentioning
confidence: 99%